Native title in Australia - Bartlett, Richard H. (Chatswood, NSW : LexisNexis, 2023)
"This comprehensive and authoritative work provides the reader with an understanding of both the current operation of native title in Australia, and its historical and political background and development. It covers the nature of the concept, and explains the proof, content and extinguishment of native title. It examines the validation of past grants and acts, and the limited degree of protection from future acts; compensation for native title; and the application of native title principles to resource development and traditional pursuits. It considers both the common law and the Native Title Act 1993 (Cth). The fifth edition of this highly regarded work includes discussion on: the consistent recognition of exclusive possession, use and enjoyment; the impact of the decisions in Northern Territory v Griffiths (HCA, 2019) and Yunupingu v Commonwealth (FCAFC, 2023) on compensation; the increasing use of consent determinations, including the Noongar South West Native Title Settlement (2016); the implications of TJIWARL and TJIWARL (No 2) (FCAFC, 2018) (BHP case) in undermining the Native Title Act future act process; the significance of the decision in Western Australia v Manado (HCA, 2020) confirming existing public access to and enjoyment of beaches on native title land; the greater adherence to principles of equality by the courts, especially as to extinguishment. Native Title in Australia provides an ideal basis for both undergraduate and postgraduate study of native title and related Aboriginal and Torres Strait Islander issues, and is a reliable and informative source for practitioners, researchers and government bodies requiring current information in this area. Features: complex topics are explained clearly and succinctly without over-simplification; critically examines native title principles as applied in the contemporary environment; engages readers to explore how native title principles are applied in practice; updated to include developments in legislation and case law."--Publisher's website.
Part 1. Background -- Ch 1. Legal History -- Ch 2. Protection and Recognition of Native Title: Mabo -- Ch 3. Political and Legislative Responses to Mabo -- Ch 4. Pastoral Leases and Equality: Wik -- Ch 5. The Ten Point Plan: Workability and the Denial of Equality -- Ch 6. Retreating from Mabo and Wik - Frozen Rights and Judicial Denial of Equality: Ward -- Ch 7. An Onerous Burden of Proof: Yorta Yorta -- Ch 8. Nigh Impossible to Prove Native Title in Urban Areas: Bennell -- Ch 9. Returning to the First Principles of Mabo and Wik in Akiba, Brown and Congoo -- Ch 10. Efficiency, Not Equality, the Focus of Legislative Change -- Ch 11. Constitutional Framework of Native Title -- Part 2. Nature of Native Title -- Ch 12. Concept of Native Title -- Ch 13. Proof -- Ch 14. Making a Claim Under the Native Title Act 1993 (Cth) -- Ch 15. Content of Native Title -- Ch 16. Transferability and Alienability -- Ch 17. Proprietary Nature of Native Title -- Part 3. Extinguishment and Validation -- Ch 18. Jurisdiction to Extinguish and Constitutional Protection -- Ch 19. Extinguishment and Impairment at Common Law: 1788-1975 -- Ch 20. Confirming or Deemed Extinguishment: 1788-1996 -- Ch 21. Extinguishment and Suspension: 1975-1996 -- Ch 22. Disregarding Historic Extinguishment -- Part 4. Future Dealings -- Ch 23. Future Act Process -- Part 5. Right to Negotiate, Agreements and Settlements, and Compensation -- Ch 24. Development of a Framework of Negotiation, Agreements and Settlements -- Ch 25. Right to Negotiate -- Ch 26. Indigenous Land Use Agreements -- Ch 27. Consent Determinations -- Ch 28. Compensation -- Part 6. Fiduciary Obligations -- Ch 29. Fiduciary Obligation as to Native Title -- Part 7. Resource Developments and Traditional Pursuits -- Ch 30. Minerals and Petroleum -- Ch 31. Water -- Ch 32. Hunting, Fishing and Gathering Rights -- Part 8. Institutions and Jurisdiction -- Ch 33. National Native Title Tribunal and the Federal Court -- Ch 34. Representative Bodies -- Ch 35. State and Territory Jurisdiction -- Part 9. Reflections on Native Title -- Ch 36. Thirty Years to a Limited Acceptance.
Includes bibliographical references and index.
Mode of access : Available online.
Keywords: Aboriginal Australians -- Land tenure; Land tenure -- Law and legislation -- Australia; Native title (Australia); Torres Strait Islanders -- Land tenure; Native title; Electronic books